ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENGARSIPAN SURAT BERBASIS WEB PADA KANTOR LURAH DESA DAYAH TUHA - Liza Rozana; Rahmat Musfikar (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2020)
An archive is an important document that is saved with a purpose when it is needed again it is easy to find it. The archive plays an important role in Dayah Tuha Village's Lurah office, so it is highly hoped that the process of managing the archives is good, fast, and easy. If the files that are owned are not well managed it will impact the difficulty of finding the information and it can impede the next stage of work. Therefore, the archive must be managed with a good and correct management system. In this research, discusses the analysis and design of a web-based document, which is suitable for the needs of the office of Tuha Village. The design of this information system based on the design of systems that have been compiled include use case diagram, activity and sequence Diaram. Dayah Tuha Village's office is still using the manual way of managing the archives. So that by the existence of this system is expected to help the work in the head office of Dayah Tuha in terms of the management of archives.